The effect of medication cost transparency alerts on prescriber behavior. (11th April 2019) - Monsen, Craig B; Liao, Joshua M; Gaster, Barak; Flynn, Kevin J; Payne, Thomas H
Abstract: Objective: The purpose of this study was to determine if medication cost transparency alerts provided at time of prescribing led ambulatory prescribers to reduce their use of low-value medications. Materials and Methods: Provider-level alerts were deployed to ambulatory practices of a single health system from February 2018 through April 2018. Practice sites included 58 primary care and 152 specialty care clinics totaling 1896 attending physicians, residents, and advanced practice nurses throughout western Washington. Prescribers in the randomly assigned intervention arm received a computerized alert whenever they ordered a medication among 4 high-cost medication classes. For each class, a lower cost, equally effective, and safe alternative was available. The primary outcome was the change in prescribing volume for each of the 4 selected medication classes during the 12-week intervention period relative to a prior 24-week baseline. Results: A total of 15 456 prescriptions for high-cost medications were written during the baseline period including 7223 in the intervention arm and 8233 in the control arm. During the intervention period, a decrease in daily prescribing volume was noted for all high-cost medications including 33% for clobetasol propionate ( p < .0001), 59% for doxycycline hyclate ( p < .0001), 43% for fluoxetine tablets ( p < .0001), and a non-significant 3% decrease for high-cost triptans ( p = .65). Prescribing volume for the high-cost medications overall decreased by 32% ( p < .0001). Conclusion: Medication cost transparency alerts in an ambulatory setting lead to more cost-conscious prescribing. Future work is needed to predict which alerts will be most effective.